1989
DOI: 10.1128/aem.55.6.1512-1518.1989
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Bacterioplankton Production and Cell Volume in a Eutrophic Estuary

Abstract: During three periods of 16 to 25 days, bacterioplankton production, bacterial cell volume, chlorophyll a, CO2 assimilation, and particulate organic carbon were measured in enclosures situated in the eutrophic estuary Roskilde Fjord, Denmark. The enclosures were manipulated with respect to sediment contact and contents of inorganic nutrients, planktivorous fish, and suspension-feeding bivalves. Nutrient enrichment, the presence of suspension feeders, and sediment contact induced pronounced changes in bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…While the biomass of the initial C. grucilis bloom was only moderately high, algal exudate from this peak may have facilitated the following large bacterial bloom (Bjornsen et al 1989;Sander and Kalff 1993). In turn, release of nutrients from the bacterial peak crash may have enabled the subsequent, large algal bloom.…”
Section: Discussionmentioning
confidence: 98%
“…While the biomass of the initial C. grucilis bloom was only moderately high, algal exudate from this peak may have facilitated the following large bacterial bloom (Bjornsen et al 1989;Sander and Kalff 1993). In turn, release of nutrients from the bacterial peak crash may have enabled the subsequent, large algal bloom.…”
Section: Discussionmentioning
confidence: 98%
“…Aroclor 1260 had an impact particularly evident on the heterotrophic component, determining a reduction of bacterial abundance (up to 80%) within 24 h. The relationship between bacterial production and cell size has been repeatedly investigated (Björnsen et al, 1989;Bird and Kalff, 1993). Recently, Servais et al (1999) and Bernard et al (2000) have shown that certain size classes have higher growth rates than others, thus, contributing to a larger fraction of bacterial C production.…”
Section: Discussionmentioning
confidence: 99%
“…7A). This is not surprising as cell activities are systematically related to cell size (Bjornsen et al 1989).…”
Section: Applicationmentioning
confidence: 93%